Teachers’ attitudes towards Computer-Assisted Language Learning in Australia and Spain - Bilbatua, Lidia; Herrero de Haro, Alfredo (Círculo de Lingüística Aplicada a la Comunicación, 2014)
A review of the existing literature shows that when it comes to studying attitudes towards CALL (Computer-Assisted Language Learning), researchers have traditionally focused on students’ perspectives and ignored teachers’ views. This study focuses on teachers’ attitudes towards CALL in order to gain a better understanding of what issues, advantages, and disadvantages teachers come across when incorporating CALL into their teaching. Furthermore, a group of teachers from Australia and Spain has been interviewed to compare how views on CALL vary across professionals in these two countries. As some authors have previously proved, the more IT literate teachers are, the more likely they are to use CALL in their teaching.